IHMT: a scientific challenging educational environment with rewarding causes - Ferrinho, Paulo (2018)
Speech at the formal opening of the academic year 2016/2017 that took place on the 21th October 2016. The author refers the broad acceptance of the IHMT educational provision, for instance in the Portuguesespeaking countries, both by attendance or e-learning. The democratization of knowledge is one of the IHMT priorities, mainly with the new Knowledge and Communication Management Office and also, at the same time, one of the challenges for the new biennium, besides investment in cooperation networks, clinical consolidation and significant contribution for a Portuguese scientific strategy towards global health and tropical diseases.